Peritoneal gliomatosis: a case report - Vaca, Enrique; Ventura, Claudia V.; Nieves, Jefferson; Acuña, Camilo; Rivera, Daniel A. (International Surgery Journal, 2021)
Peritoneal gliomatosis is the mature neuroglial tissue in peritoneum, this is commonly associated with immature teratoma. Can be associated with ascites alone or ascites and pleural effusion in which case it is called pseudo Meigs syndrome, the lymph node invasion has been described. In the imaging studies such computed tomography they can be show as multiple peritoneal nodules, the positron emission tomography has shown utility in cases of doubt of recurrence of mature teratoma without evidence of primary tumor with elevated tumor marker. The initial treatment depends on the treatment of the teratoma, reserving the surgical treatment of the peritoneal gliomatosis in the presence of complications related to the implants. A 21-year-old woman without chronic degenerative disease story with clinical presentation of abdominal distension, a CT scan is performed that shows a right ovary tumor; a laparotomy was performed in which ascites and peritoneal nodules were evidenced suggesting the presence of carcinomatosis. Histopathological study demonstrated peritoneal gliomatosis.